Etnomatematika pada Kain Tapis dan Rumah Adat Lampung - Loviana, Selvi; Merliza, Pika; Damayanti, Arlina; Mahfud, Muhammad Khoirudin; Islamuddin, Anang Ma'ruf (Tapis: Jurnal Penelitian Ilmiah, 2020)
Many students find it difficult to learn mathematics. This is partly due to the view that mathematics is far from real-life and culture. Whereas, in real life, mathematics is very closely related to the reality of life, one of which is culture. In Lampung's culture, mathematics is presented in many ways such as buildings and others. This research was conducted to increase awareness that the concept of mathematics is very close and related to the cultural value of the community through the exploration of the ethnomathematics concept which has been practiced by the Lampung community, especially on Tapis and traditional houses. Based on the results of the study, it was found that the concept of Tapis and traditional houses of Lampung have used the concept of mathematics, such as a flat structure. The concept of mathematics in Lampung cultural values ​​is expected to be used as a source of learning mathematics in school as well as being expected to increase students' love for local culture.